1991
DOI: 10.1007/bf00054751
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience of coenzyme Q10 to enhance intraoperative myocardial protection in coronary artery revascularization

Abstract: Seventy-eight patients undergoing coronary artery bypass grafting (CABG) were compared retrospectively to evaluate whether pretreatment with coenzyme Q10 (CoQ) is effective in preventing left ventricular depression in early reperfusion following CABG. CoQ (5 mg/kg, intravenously) was given to 60 patients, 2 hours prior to the onset of cardiopulmonary bypass (CPB). CABG was performed using saphenous vein under CPB associated with cold cardioplegia in the standard fashion. Heart rate, mean arterial pressure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The coenzyme Q10 dose, used in our experiment (a total intracoronary administered dose of 36 mg CoQ10 in these experiments), was comparable to the dose used in other studies that reported beneficial effects of acute administration of CoQ10 (5-15 mg/kg), (9,(18)(19)(20)22,23). It was reported earlier that the CoQ10 content of the myocardium increased in a dosedependent manner at 60 min after the intravenous infusion of 5 or 15 mg/kg CoQ10 (23).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The coenzyme Q10 dose, used in our experiment (a total intracoronary administered dose of 36 mg CoQ10 in these experiments), was comparable to the dose used in other studies that reported beneficial effects of acute administration of CoQ10 (5-15 mg/kg), (9,(18)(19)(20)22,23). It was reported earlier that the CoQ10 content of the myocardium increased in a dosedependent manner at 60 min after the intravenous infusion of 5 or 15 mg/kg CoQ10 (23).…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that myocardial CoQ10 and CoQ10-reductase levels are reduced in chronic cardiac failure (9), ischemia-reperfusion injury (6,10,11), cardiomyopathy (6), and other heart diseases (4,(12)(13)(14). Also, levels of CoQ10 decreased during therapy with HMG-CoA reductase inhibitors, gemfibrozil, adriamycin, and certain beta-blockers (4).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, a rapidly escalating number of reports have appeared on attempts to treat "cardiomyopathy" with compounds with antioxidant action, in particular coenzyme Q (87)(88)(89)(90)(91)(92). While some of the reports may be promising, such treatment is yet to be established.…”
Section: Age-related Degenerative Diseases and Defects In Oxidative Pmentioning
confidence: 99%
“…In patients undergoing CABG pretreatment with intravenous CoQ10 (5 mg/kg, intravenously 2 hours before cardiopulmonary bypass) prevents left ventricular depression in early reperfusion and minimizes myocardial cellular injury during CABG following reperfusion. (17) In comparison with younger individuals, the outcome of surgery in the elderly, is compromised by age-related reduction of cellular energy production in the myocardium d u r i n g s u r g e r y . F i b e r s f r o m s u b j e c t s o v e r age 70 showed poor recovery of force after simulated ischemia compared to younger patients.…”
Section: Coenzyme Q10mentioning
confidence: 99%